Peran Kualitas Pelayanan, Variasi Produk, dan Customer Experience (Studi Kasus pada Toko Grosir Salsa Motoris). : Studi Kasus pada Toko Grosir Salsa Motoris - Kuwatno Kuwatno; Setya Pramono (Journal Of Business, Finance, and Economics (JBFE), 2025)
This research aims to determine the effect of service quality, product variety, and customer experience on customer loyalty at the Salsa Motoris wholesale store. This study used 100 respondents, the data collection process was carried out by distributing questionnaires using the google form link to all consumers who make repeat purchase at salsa motoris wholesale store. This study uses multiple linear regression analysis methods with statistical test tools. The measurements in this study used a Likert scale and data processing in this study using IBM SPSS 26. The results of this research indicate that service quality has a positive and significant effect on customer loyalty, product variety has a positive and significant effect on customer loyalty, and customer experience has a positive and significant effect on customer loyalty. Service quality, product variety, and costumer experience have a positive and significant influence on customer loyalty, in the F test count of 118,553> from the F table value of 2.70 and a significant value of 0.000 service quality, product variety, and costumer experience there is a positive and significant influence on customer loyalty.